Osteochondroma Arising from the Thyroid Cartilage: A Case Report and Literature Review - Miller, Jessa E.; Azar, Shaghauyegh S.; Chhetri, Dinesh K. (Case Reports in Otolaryngology, 2021)
Introduction. Osteochondromas are relatively common benign bone tumors often located at the metaphyseal ends of long bones; however, they are rare in the head and neck region. The objective of this study is to present a case of an osteochondroma arising from the thyroid cartilage causing insidious dysphonia and to present a literature review. Methods. The medical record of a patient treated for osteochondroma of the thyroid cartilage was reviewed. A literature search on osteochondromas was conducted using PubMed and Google Scholar. The epidemiology, presentation, diagnosis, treatment, and outcomes of osteochondromas were reviewed. Results. A 50-year-old female presented with nine months of dysphonia and aphonic voice breaks. Laryngovideostroboscopy revealed a left false vocal fold fullness, glottal gap, and vibratory phase asymmetry. A CT neck demonstrated a well-circumscribed 5 × 8 × 9 mm mass arising from the left thyroid cartilage lamina with a thin calcified rim and a heterogeneous decreased attenuation center. The tumor was excised surgically. Histopathologic analysis demonstrated hyaline cartilage overlying lamellar bone with fatty bone marrow, consistent with osteochondroma. English language literature review revealed no cases of osteochondroma of the thyroid cartilage. The presenting features of osteochondroma may depend on the size and location of the lesion. It is critical to differentiate between benign and malignant bone tumors, and physicians must rely on their clinical examination, radiographic findings, and histopathologic analysis to make the correct diagnosis. Conclusions. Osteochondromas of the laryngeal framework are extremely rare, and to our knowledge, there have been no reports in the literature of this tumor arising from the thyroid cartilage. Dysphonia may be the presenting symptom in a patient with a thyroid cartilage mass causing restricted mobility of the true vocal folds.